Development and Validation of Onhan Supplementary Learning Module on Four Basic Operations on Integers - Rapada, Sherwin; Servañez, Bilshan (Romblon State University Research Journal, 2024)
Mathematics has been proven to be a difficult subject for students. At Ferrol National High School, the student proficiency in quarterly periodical test was 56.28% as against the 75% standards. This study developed an Onhan supplementary module on operations on integers to provide struggling learners the chance to learn operations on integers using the learners’ first language as the medium which students under open high schools in other Onhan-speaking municipalities can also use. The developed material underwent validation from five content experts based from the DepEd’s guidelines and processes for Learning Resource Management and Development System’s predetermined criteria. The materials were further assessed by two Onhan language experts, selected intended users, and pilot tested to grade seven students. The result of the validation revealed that the developed Onhan supplementary learning module was very satisfactory (M=3.76). The comparison of pretest and posttest of students’ scores after pilot testing showed a significant mean difference, with the post-test recording 9.6% points higher than the target of 75%. This implies that the developed supplementary module contributed to the improvement of the performance of the students in operations on integers, (t=-11.511, p=.000). Furthermore, the words and sentences used in the developed Onhan supplementary learning readability were found appropriate for Grade 9 and may be adjusted to fit the target users.